Stop Tobacco Circus - Abd Razak, Dzulkifli (2005)
ON Tuesday, May 31, we will be celebrating the 2005 World NoTobacco Day (WNTD), a day to look back and check the Key Performance Indices (KPIs) in our attempt to butt out the deadly smoking habit in Malaysia over the last year. It is also a day of stern reminder for smokers to quit their dangerous habit. Increasingly, WNTD has become more important for Asia, being the last frontier for the tobacco industry, which has been booted put of their (Western) countries of origin. A recent global report suggests that cigarette production per person has fallen to its lowest level since 1972, which makes the tobacco industry desperate for new markets. Asia, already the region with the largest number of smokers, is a convenient target since the level of awareness of its population is generally low.